Internally Financed Working Capital: Top Manager Preferences from the Perspective of Gender - Sunardi Sunardi; Theresia Woro Damayanti; Supramono Supramono (Universitas Hayam Wuruk Perbanas, 2020)
This study seeks to investigate the differences in firm managers’ preferences in the use of internal funding to meet working capital needs. The data to be analyzed are obtained from the results of the World Bank's Productivity and the Investment Climate Survey on firm managers in 98 developing countries, with a total sample of 1,235 firm managers. The analysis techniques used are linear regression and ordinal logit analysis. This study demonstrates the gender-based differences in the proportion of the use of internal funding sources. Female top managers prefer to use internal funding sources for working capital better than top male managers. This study not only provides a better understanding of the relationship between the existence of top female managers and the preference in the use of internally financed working capital but also informs firms that aim to balance the liquidity and the capital cost efficiency in managing their working capital to provide a more significant opportunity for women to occupy top management positions.